Reversed Effects of Intermittent Theta Burst Stimulation following Motor Training That Vary as a Function of Training-Induced Changes in Corticospinal Excitability. (17th June 2015) - Stöckel, Tino; Summers, Jeffery J.; Hinder, Mark R.
Abstract : Intermittent theta burst stimulation (iTBS) has the potential to enhance corticospinal excitability (CSE) and subsequent motor learning. However, the effects of iTBS following motor learning are unknown. The purpose of the present study was to explore the effect of iTBS on CSE and performance following motor learning. Therefore twenty-four healthy participants practiced a ballistic motor task for a total of 150 movements. iTBS was subsequently applied to the trained motor cortex (STIM group) or the vertex (SHAM group). Performance and CSE were assessed before motor learning and before and after iTBS. Training significantly increased performance and CSE in both groups. In STIM group participants, subsequent iTBS significantly reduced motor performance with smaller reductions in CSE. CSE changes as a result of motor learning were negatively correlated with both the CSE changes and performance changes as a result of iTBS. No significant effects of iTBS were found for SHAM group participants. We conclude that iTBS has the potential to degrade prior motor learning as a function of training-induced CSE changes. That means the expected LTP-like effects of iTBS are reversed following motor learning.